2000
DOI: 10.1200/jco.2000.18.12.2444
|View full text |Cite
|
Sign up to set email alerts
|

High- and Low-Dose Interferon Alfa-2b in High-Risk Melanoma: First Analysis of Intergroup Trial E1690/S9111/C9190

Abstract: The results of the intergroup E1690 trial demonstrate an RFS benefit of IFNalpha2b that is dose-dependent and significant for HDI by Cox multivariable analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
445
3
15

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 836 publications
(475 citation statements)
references
References 12 publications
12
445
3
15
Order By: Relevance
“…The authors reported a clear disease-free survival advantage for the patients given interferon, but there were insufficient deaths observed during the relatively short follow-up period to evaluate any effect on survival. The next ECOG study, E1690, compared the high-dose Kirkwood regimen with 2 years of 3 MU interferon given subcutaneously 3 times a week, and an observation only group (Kirkwood et al, 2000a). In contrast to the earlier E1684 study, E1690 has not demonstrated a survival advantage for either treatment arm as compared to the control observation arm, but has reported a statistically significant disease-free survival advantage for the high-dose regimen as compared with the observation arm (hazard ratio 1.28, P = 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported a clear disease-free survival advantage for the patients given interferon, but there were insufficient deaths observed during the relatively short follow-up period to evaluate any effect on survival. The next ECOG study, E1690, compared the high-dose Kirkwood regimen with 2 years of 3 MU interferon given subcutaneously 3 times a week, and an observation only group (Kirkwood et al, 2000a). In contrast to the earlier E1684 study, E1690 has not demonstrated a survival advantage for either treatment arm as compared to the control observation arm, but has reported a statistically significant disease-free survival advantage for the high-dose regimen as compared with the observation arm (hazard ratio 1.28, P = 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…4 The E2690 Intergroup laboratory corollary study included 148 of 642 patients who entered Trial E1690. Immunologic data for at least one of the four time points prior to the end of the study period were obtained for 143 of these patients, who comprised the current study population for phenotypic and functional assays.…”
Section: Methodsmentioning
confidence: 99%
“…2 The Eastern Cooperative Oncology Group (ECOG) and the United States Intergroup, which is comprised of the ECOG, the Southwest Oncology Group, and Cancer and Leukemia Group B (CALGB) along with the M. D. Anderson Cancer Center, have established the benefit of chemotherapy with interferon ␣2b (IFN␣2b) at high doses (HDI) in four prospective clinical trials. [3][4][5][6] Those trials enrolled more than 1900 patients with deep primary melanoma (AJCC Stage IIB), regionally metastatic melanoma (AJCC Stage III), or recurrent melanoma involving regional lymph nodes, and a consistent reduction was demonstrated in the recurrence of melanoma at all sites, with a significant prolongation of survival for the participants in two of those trials. The toxicity of HDI therapy has been an obstacle to its application, and features of the disease or patient characteristics that may predict response to this therapy have been sought to improve its therapeutic index.…”
mentioning
confidence: 99%
“…The consensus panel identified two immunotherapy agents with potential clinical benefit in the adjuvant therapy of patients with stage III melanoma: interferon-α2b and pegylated-interferon-α2b. 4,[24][25][26][27] Consensus management of microscopic nodal disease The panel recognized that patients with microscopically involved lymph nodes (N1a disease) might represent a different population than those with macroscopic nodal disease (N1b and N2-N3 disease). A majority (52.2%) of the panel recommends a standard 1-year course of interferon-α2b for the adjuvant therapy of microscopic nodal disease.…”
Section: Initial Assessmentmentioning
confidence: 99%
“…26 Subsequent randomized studies confirmed a benefit in relapse-free survival, but results indicating an overall survival benefit were inconsistent. 25,33 Several metaanalyses evaluated the clinical benefits of interferon-α2b and indicate a benefit in relapse-free survival and a trend toward improved overall survival. [29][30][31] The panel generally considered the data to provide level A evidence for a benefit in relapse-free survival with level B support for an improvement in overall survival from treatment with interferon-α2b.…”
Section: Literature Review and Analysismentioning
confidence: 99%